Early closure of initial gaps in the bone–tray interface of modern cementless total knee arthroplasty: A retrospective cohort study - Yoshinori Mikashima; Hitoshi Imamura; Koichiro Yano; Katsunori Ikari; Hiroshi Takagi; Ken Okazaki (Journal of Joint Surgery and Research)
Purpose: Initial gaps in the tibial bone–tray interface may sometimes occur due to insufficient impaction, especially on hard tibial bone. The purpose of this study was to investigate the frequency of occurrence, characteristics, and natural history of initial gaps between the tibial bone–tray interface during surgery in a modern cementless total knee arthroplasty (TKA). Methods: A retrospective review of a consecutive series of 273 cementless posterior stabilized mobile-bearing TKAs (Attune; DePuy Synthes, Warsaw, IN, USA) was performed. The incidence of gaps between the tibial bone and tibial tray that remained open during surgery was reviewed immediately after surgery and at 1 week, 1, 2, 4, and, 6 months, and 1 year post-operatively. The 273 TKAs were divided into two groups: TKAs with initial gaps (Group G) and those without gaps (Group N). Results: Initial gaps appeared in 26 of the 273 TKAs (9.5%) on radiographs immediately after surgery. Four of 26 TKAs (15%) showed initial gaps that naturally disappeared due to weight-bearing at 1 week post-operatively, 16 of 26 TKAs (62%) within 1 month post-operatively, 20 of 26 TKAs (77%) within 2 months post-operatively, and all 26 TKAs (100%) within 4 months post-operatively. Group G included significantly younger patients (p ​< ​0.01) with a higher body mass index (p ​< ​0.01) than Group N. No patients required revision surgery. Conclusion: The majority of initial gaps at the tibial bone–tray interface were resolved early during follow-up in a modern, cementless, posterior stabilized, mobile-bearing TKA.